Self-Efficacy and Pedagogical Competence of Preservice English Teacher Students:A Correlational Study - Yulia Eka Sari; Fernandita Gusweni Jayanti; Muhammad Fadhli (UNIB Press, 2026)
Self-efficacy and pedagogical competence are abilities that preservice English teacher students must possess. The aim of this research was to investigate the levels of self-efficacy and pedagogical competence and their correlation. This research used a quantitative correlational design. The participants in this research were 127 preservice English teacher students. The research instrument was a self-report questionnaire survey. The data analysis techniques used in this research were descriptive analysis and non-parametric Spearman correlation with SPSS software. The findings of this research revealed that preservice English teacher students have high levels of self-efficacy and pedagogical competence, and there is a significant correlation between the two variables. A preservice teacher must not only be proficient in pedagogical competence but also be confident in their abilities to face challenges in the workplace and become a professional teacher.